Sodium arsenite-induced changes in the wood of esca-diseased grapevine at cytological and metabolomic levels - Trouvelot, Sophie; Lemaitre-Guillier, Christelle; Vallet, Julie; Jacquens, Lucile; Douillet, Antonin; Harir, Mourad; Larignon, Philippe; Roullier-Gall, Chloé; Schmitt-Kopplin, Philippe; Adrian, Marielle; Fontaine, Florence (Frontiers in Plant Science, 2023)
In the past, most grapevine trunk diseases (GTDs) have been controlled by treatments with sodium arsenite. For obvious reasons, sodium arsenite was banned in vineyards, and consequently, the management of GTDs is difficult due to the lack of methods with similar effectiveness. Sodium arsenite is known to have a fungicide effect and to affect the leaf physiology, but its effect on the woody tissues where the GTD pathogens are present is still poorly understood. This study thus focuses on the effect of sodium arsenite in woody tissues, particularly in the interaction area between asymptomatic wood and necrotic wood resulting from the GTD pathogens’ activities. Metabolomics was used to obtain a metabolite fingerprint of sodium arsenite treatment and microscopy to visualize its effects at the histo-cytological level. The main results are that sodium arsenite impacts both metabolome and structural barriers in plant wood. We reported a stimulator effect on plant secondary metabolites in the wood, which add to its fungicide effect. Moreover, the pattern of some phytotoxins is affected, suggesting the possible effect of sodium arsenite in the pathogen metabolism and/or plant detoxification process. This study brings new elements to understanding the mode of action of sodium arsenite, which is useful in developing sustainable and eco-friendly strategies to better manage GTDs.